EFEKTIVITAS PRINSIP TRADE RELATED ASPECTS OF INTELLECTUAL PROPERTY RIGHTS DAN AGREEMENT TECHNICAL BARRIERS TO TRADE DALAM PEMBERIAN PERLINDUNGAN HUKUM TERHADAP PRODUK ROKOK INDONESIA DI AUSTRALIA ATAS PELAKSANAAN ASAS KETERTIBAN UMUM - Sri Mastuti (Jurnal Hukum dan Bisnis (Selisik), 2018)
Indonesians are protesting the plain packaging policy by Australia which requires thatcigarette packaging be made not to contain logos,manufacturers. This policy by Indonesia isconsidered to violate the provisions of trade relataspects of intellectual property rights andtechnical barriers to trade agreement in the provision of petrochemical legal protection ofIndonesian cigarette products.The Australian policy is intended to protect the health of itscitizens caused by tobacco.This study aims to determine the history on the effectiviteness ofTRIPs and ATBT principle in the legal protection of intellectual property protection, publicorder link with TRIPs and ATBT in legal protection for intellectual property and cigaretteprotection for intellectual property and cigar Indonesia as well as the benefits of TRIPs andATBT for the future of Indonesian cigarette exports. This research uses normative juridicialTheconclusion of this study that all matters relating to the protection of intellectual property law andtrade barriers should not be contrary to public order